Playing-related musculoskeletal disorders among Chinese conservatoire piano students: prevalence, risk factors and preventive interventions - Zhao, Luqian; Wang, Yafei; Zhang, Zheren (Frontiers in Psychology, 2024)
Playing-related musculoskeletal disorders (PRMDs) are a common issue among musicians during their whole career life (Austen, 2020). Both professional musicians and conservatoire students who are receiving professional training are at significant risk of developing PRMDs (Allsop, 2010). With the growing number of students pursuing a conservatory degree and graduating from music conservatory in China, the aims of this study were: (1) to identify the nature of PRMD and explore the prevalence of PRMD in Chinese conservatoire students; (2) to determine the relevant risk factors with the presence of PRMD among Chinese conservatoire students; and (3) to suggest interventive preventions for young pianists at their early career stage. A self-reported online survey study was conducted among 363 Chinese conservatoire students who majored in piano performance. Of all respondents, 82.6% reported having had at least one PRMD. The wrist was proved to be the most affected body site, followed by the shoulder, finger and arm. Respondents who experienced PRMD reported “pain”, “fatigue”, and “stiffness” as the most frequent symptoms. The main risk factors associated with PRMD included gender, years of playing experiences, practice hours, warm-up habits before practice, and break-taking during practice. Female students, those with longer year of playing experience, those who practice longer hours, those who do not warm up before practice, and those who do not take breaks during practice were found to have more PRMD symptoms and higher level of severity. This study highlights the need to increase awareness of PRMD among conservatoire students and to understand the occurrence of PRMD; it is helpful for young pianists to prevent severe musculoskeletal disorders and implement preventative measures at early career stages. Further studies are suggested to follow up on music students who have had at least one PRMD at different stages of professional musical training.